2017
DOI: 10.1039/c7cp04527a
|View full text |Cite
|
Sign up to set email alerts
|

Surface pKa of octanoic, nonanoic, and decanoic fatty acids at the air–water interface: applications to atmospheric aerosol chemistry

Abstract: There exists large uncertainty in the literature as to the pK of medium-chain fatty acids at the air-water interface. Via surface tension titration, the surface-pK values of octanoic (C), nonanoic (C), and decanoic (C) fatty acids are determined to be 4.9, 5.8, and 6.4, respectively. The surface-pK determined with surface tension differs from the bulk value obtained during a standard acid-base titration. Near the surface-pK of the C and C systems, surface tension minima are observed and are attributed to the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
114
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(123 citation statements)
references
References 59 publications
9
114
0
Order By: Relevance
“…Several experimental studies have identified increased pK a values for acid groups present at surfaces and interfaces, including self-assembled monolayers [51], fatty acid micelles [52,53] and, more recently, at the air/water interface for fatty acid monolayers [54], the latter study also identifying the effect of chain length on the magnitude of the pK a change. In the context of the present paper, this will mean that adsorbed NA molecules will remain largely undissociated as the effective (interfacial) pK a is higher than the pH of the aqueous solutions.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Several experimental studies have identified increased pK a values for acid groups present at surfaces and interfaces, including self-assembled monolayers [51], fatty acid micelles [52,53] and, more recently, at the air/water interface for fatty acid monolayers [54], the latter study also identifying the effect of chain length on the magnitude of the pK a change. In the context of the present paper, this will mean that adsorbed NA molecules will remain largely undissociated as the effective (interfacial) pK a is higher than the pH of the aqueous solutions.…”
Section: Resultsmentioning
confidence: 93%
“…more recently, at the air/water interface for fatty acid monolayers [54], the latter study also identifying the effect of chain length on the magnitude of the pKa change. In the context of the present paper, this will mean that adsorbed NA molecules will remain largely undissociated as the effective (interfacial) pKa is higher than the pH of the aqueous solutions.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the longer fatty acids will dominate the lateral interactions in the SSA film, making the film more rigid due to the greater sum of dispersion interactions [66,73,74]. Carboxylic acid head groups of long chain fatty acids (>C 14 ) are only partially deprotonated at high pH due to their relatively high surface pK a values [75,76]. However, cation-head group interactions slightly moderate the pK a increase associated with increasing alkyl chain length [76].…”
Section: Introductionmentioning
confidence: 99%
“…Carboxylic acid head groups of long chain fatty acids (>C 14 ) are only partially deprotonated at high pH due to their relatively high surface pK a values [75,76]. However, cation-head group interactions slightly moderate the pK a increase associated with increasing alkyl chain length [76]. As SSA ages in the marine boundary layer (MBL), the particles interact with trace gases that lower the pH of the particle aqueous core.…”
Section: Introductionmentioning
confidence: 99%
“…For the case in which the DpK a value was above 20, the T d exceeded 4508C under an N 2 atmosphere. [10] Table 1 summarises the DpK a values for this study, which were determined via the following equation: DpK a ¼ pK a of DBUH þ (13.28) -pK a of carboxylic acid [13][14][15] (see Table 1). Since the DpK a values of the PILs synthesised in this study are between 6.88 and 9.51, it is likely that proton transfer (neutralisation) insufficiently occurs during the synthesis of PILs.…”
Section: Thermal Properties Of Pilsmentioning
confidence: 99%